2017
DOI: 10.1053/j.jrn.2017.04.006
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Subjective Global Assessment and Protein Energy Wasting Score to Nutrition Evaluations Conducted by Registered Dietitian Nutritionists in Identifying Protein Energy Wasting Risk in Maintenance Hemodialysis Patients

Abstract: Objective The study compared the 7-point Subjective Global Assessment (SGA) and the Protein Energy Wasting (PEW) Score with Nutrition Evaluations (NutrE) conducted by registered dietitian nutritionists (RDNs) in identifying PEW risk in stage five chronic kidney disease (CKD) patients on maintenance hemodialysis (MHD). Design and Methods This study is a secondary analysis of a cross-sectional study entitled “Development and Validation of a Predictive energy Equation in Hemodialysis”. PEW risk identified by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…Nutritional status was maintained during the intervention and on starting dialysis, which is encouraging considering that CKD and dialysis are commonly associated with reduced nutritional status, protein energy wasting (PEW), muscle wasting and sarcopenia, (Fouque et al 2011;Carrerro et al 2013;Cupisti et al 2013). Both HGS and SGA are considered valid and reliable markers of functional and nutritional status, and predict morbidity and mortality in CKD (Steiber et al 2007;Chang et al 2011;Cuppari et al 2014;Dai et al 2017;Sum et al 2017), and these were maintained in our study. Previous studies comparing different nutritional interventions, particularly in pre-dialysis CKD, are scarce, however Campbell et al (2008) found that a 12-week nutritional intervention programme improved nutritional status and HRQoL, possibly due to increased frequency of patient follow-up and more regular adjustments in nutritional treatment.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Nutritional status was maintained during the intervention and on starting dialysis, which is encouraging considering that CKD and dialysis are commonly associated with reduced nutritional status, protein energy wasting (PEW), muscle wasting and sarcopenia, (Fouque et al 2011;Carrerro et al 2013;Cupisti et al 2013). Both HGS and SGA are considered valid and reliable markers of functional and nutritional status, and predict morbidity and mortality in CKD (Steiber et al 2007;Chang et al 2011;Cuppari et al 2014;Dai et al 2017;Sum et al 2017), and these were maintained in our study. Previous studies comparing different nutritional interventions, particularly in pre-dialysis CKD, are scarce, however Campbell et al (2008) found that a 12-week nutritional intervention programme improved nutritional status and HRQoL, possibly due to increased frequency of patient follow-up and more regular adjustments in nutritional treatment.…”
Section: Discussionsupporting
confidence: 68%
“…; Sum et al . ), and these were maintained in our study. Previous studies comparing different nutritional interventions, particularly in pre‐dialysis CKD, are scarce, however Campbell et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, there are various causes of PEW in patients with kidney disease, and SGA is a recommended tool for nutritional assessment but not a tool to identify PEW since SGA alone does not provide any insight into the different causes of PEW. [ 4 , 40 ] This disassociation might be found between younger and older patient groups.…”
Section: Discussionmentioning
confidence: 97%
“…The following elements were considered and integrated: Nutritional markers and integrated scores (albumin, pre-albumin, cholesterol; body size, Body mass index (BMI), Malnutrition Inflammation Score (MIS), Subjective Global Assessment (SGA)) [ 43 , 44 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]; Life expectancy: age, comorbidity (Charlson Index), and dialysis vintage [ 60 , 63 ]; Kinetic goals (Kt/V; n-PCR; calcium phosphate and PTH control; beta-2 microglobulin levels) [ 16 , 19 , 20 , 21 , 22 ]; Technical aspects: vascular access (fistula versus catheter, degree of functionality, problems found) [ 64 , 65 ]; Residual kidney function, weight gain [ 66 , 67 , 68 ]; Dialysis tolerance (intradialysis hypotension, post-dialysis fatigue and subjective evaluation of the effect of dialysis on quality of life) [ 69 ]. …”
Section: Tolerance Beyond Depurationmentioning
confidence: 99%